2019
DOI: 10.1002/jtr.2303
|View full text |Cite
|
Sign up to set email alerts
|

Examining medical tourists' intention to visit a tourist destination: Application of an extended MEDTOUR scale in a cosmetic tourism context

Abstract: Behavioral studies of medical tourists are still limited despite a recent and rapid boom in both the business and academic fields. In 2011, Martin, Ramamonjiarivelo, and Martin proposed their MEDTOUR scale to better understand medical tourists' intention to seek treatment overseas. However, the scale has not been validated through application in a different context to date. The present study aims to fill this gap by examining its reliability and applying it in an extended model with perceived risk and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 61 publications
(110 reference statements)
3
26
0
Order By: Relevance
“…Our finding of a relatively weak relationship between residents’ PBC and AB (supporting H5 ) reinforces the results of previous studies (Liang et al , 2019; Zhang and Wang, 2019). Liang et al (2019) found that tourists’ PBC was related to their attitude towards a tourist destination.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our finding of a relatively weak relationship between residents’ PBC and AB (supporting H5 ) reinforces the results of previous studies (Liang et al , 2019; Zhang and Wang, 2019). Liang et al (2019) found that tourists’ PBC was related to their attitude towards a tourist destination.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a relatively weak relationship between residents’ PBC and AB (supporting H5 ) reinforces the results of previous studies (Liang et al , 2019; Zhang and Wang, 2019). Liang et al (2019) found that tourists’ PBC was related to their attitude towards a tourist destination. Similarly, Zhang and Wang (2019) confirmed that tourists’ PBC had a significant impact on their rural tourism attitudes, although it was the weakest predictor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations